Pengaruh partisipasi masyarakat terhadap penyaluran dana (landing) Bank Syariah - Agustina, Asiroch Yulia; Khairunnisa, Khairunnisa; Khoyriyah, Khoyriyah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The development of Islamic banks in Indonesia is seen as fairly substantial, but funding distribution goods have not kept pace (landing). Therefore, the objective of this study was to assess the impact of knowledge, income, and views on the distribution of funds in Islamic banks, particularly among the residents of Bangkalan Regency. This study employed a quantitative research method, which means that the data obtained is numerical or in numerical form. With a total of 100 respondents, the population of Bangkalan Regency serves as the sample population for this study. Consequently, H1 is accepted, as demonstrated by the fact that Tcount is more than T Table (2,744 > 1,660) H2 is acceptable because income has a substantial impact on the distribution of funds in Islamic institutions, as demonstrated by a T-count value greater than T-table (4,733 > 1,660). Also, income has a substantial effect on the distribution of money in Islamic institutions, therefore H2 is accepted, as shown by the fact that Tcount is bigger than Ttable (4,733 > 1,660). H3 is supported by the fact that Tcount is bigger than Ttable (3.924 > 1.660), indicating that perception has a considerable impact on the distribution of funds in Islamic institutions.